Pengaruh Lingkungan Kerja dan Karakteristik Pekerjaan terhadap Burnout, Kepuasan Kerja, Komitmen Organisasi dan Intention to Leave (Studi pada Pegawai Perum Pegadaian di Sulawesi Utara) - Bogar, Wilson (Universitas Brawijaya, Indonesia, 2011)
The purpose of this study is to analyze and explain the effect of work environment and job characteristics toward burnoul, job satisfaction, organizational commitment, and intention to leave. This research is explanatory research and cross-sectional research design. The Samples taken by proportional stratified random sampling technique and the size to be determined 132 employees out of 196 Perum Pegadaian 's employees in North Sulawesi. Data Collecting technique is questionnaire. Data were analyzed by using Structural Equation Modeling (SEM) analysis. The results of this study showed: (1) The work environment has significantly effect toward burnout, job satisfaction, organizational commitment, and intention to leave, (2) Job characteristics have significantly effect toward burnout and job satisfaction, but it have not significantly effect toward organizational commitment and intention to leave. (3) Burnout has significantly effects toward job satisfaction, organizational commitment, and intention to leave, (4) Job satisfaction has significantly effect toward organizational commitment, but it has not significantly effect toward intention to leave, (5) organizational commitment has significantly effect toward intention to leave.